Involvement of Ca2+-activated K+ channel 3.1 in hypoxia-induced pulmonary arterial hypertension and therapeutic effects of TRAM-34 in rats. Issue 4 (27th July 2017) - Guo, Shujin; Shen, Yongchun; He, Guangming; Wang, Tao; Xu, Dan; Wen, Fuqiang
Abstract : Pulmonary artery hypertension (PAH) is an incurable disease associated with the proliferation of pulmonary artery smooth muscle cells (PASMCs) and vascular remodeling. The present study examined whether TRAM-34, a highly selective blocker of calcium-activated potassium channel 3.1 (Kca3.1), can help prevent such hypertension by reducing proliferation in PASMCs. Rats were exposed to hypoxia (10% O2 ) for 3 weeks and treated daily with TRAM-34 intraperitoneally from the first day of hypoxia. Animals were killed and examined for vascular hypertrophy, Kca3.1 expression, and downstream signaling pathways. In addition, primary cultures of rat PASMCs were exposed to hypoxia (3% O2 ) or normoxia (21% O2 ) for 24 h in the presence of TRAM-34 or siRNA against Kca3.1. Activation of cell signaling pathways was examined using Western blot analysis. In animal experiments, hypoxia triggered significant medial hypertrophy of pulmonary arterioles and right ventricular hypertrophy, and it significantly increased pulmonary artery pressure, Kca3.1 mRNA levels and ERK/p38 MAP kinase signaling. These effects were attenuated in the presence of TRAM-34. In cell culture experiments, blocking Kca3.1 using TRAM-34 or siRNA inhibited hypoxia-induced ERK/p38 signaling. Kca3.1 may play a role in the development of PAH by activating ERK/p38 MAP kinase signaling, which may then contribute to hypoxia-induced pulmonary vascular remodeling. TRAM-34 may protect against hypoxia-induced PAH.